On the Anisotropic Accuracy Analysis of ACM's Nonconforming Finite Element (Journal of Computational Mathematics, 2021)
The main aim of this paper is to study the superconvergence accuracy analysis of the famous ACM's nonconforming finite element for biharmonic equation under anisotropic meshes. By using some novel approaches and techniques, the optimal anisotropic interpolation error and consistency error estimates are obtained. The global error is of order $O(h^2)$. Lastly, some numerical tests are presented to verify the theoretical analysis.